2021
DOI: 10.20471/acc.2021.60.04.10
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Coherence and Subjective Well-Being among Adolescents – The Potential Impact of Living in a Dormitory Compared to Living with Family

Abstract: SUMMARY The aim of the study was to analyze the relationship between the sense of coherence (SOC) and subjective well-being (SWB) as a health promoting resource among adolescents living with parents and those living in dormitories. There were 442 adolescent responders, yielding a response rate of 84.3%. The SOC was measured using the Orientation to Life Questionnaire, while SWB was obtained from the Personal Wellbeing Index. There were no significant differences between the group living with parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…The implementation of these interventions may largely be responsible for building a high SoC capacities among females in Northern Ghana, hence the finding of the current study. Contrary results have been found in some studies that males have higher SoC than females [26,50,51]. Other research evidence has also reported no differences in SoC across genders [34,54,56,57].…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…The implementation of these interventions may largely be responsible for building a high SoC capacities among females in Northern Ghana, hence the finding of the current study. Contrary results have been found in some studies that males have higher SoC than females [26,50,51]. Other research evidence has also reported no differences in SoC across genders [34,54,56,57].…”
Section: Discussioncontrasting
confidence: 59%
“…Several reports have shown female experience SWB better than male students in Spain [23] and Norway [24]. Contrary results have been found in Italy [25], Croatia [26], Norway [27,28], China [29], and Nigeria [30]. Others reported no gender differences in Hungary [22], Turkey [31], and Israel [32].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…This is directly connected with the understanding of the justified ties between the situations or events and personal action, which we shall describe here as the feeling of meaningfulness. It fulfils a significant role in shaping the relations between a situation, stress (including anxiety), an individual response, and the adjustable mechanisms of the entity [ 2 ]; simultaneously, this notion is consistent with the concept of the intricate approach to the issue of a healthy lifestyle [ 3 ] and is treated as one of the predictors of mental health [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 92%